Genome-Wide Association Studies Reveal the Genetic Basis of Ionomic Variation in Rice. Issue 11 (29th October 2018) - Yang, Meng; Lu, Kai; Zhao, Fang-Jie; Xie, Weibo; Ramakrishna, Priya; Wang, Guangyuan; Du, Qingqing; Liang, Limin; Sun, Cuiju; Zhao, Hu; Zhang, Zhanyi; Liu, Zonghao; et al.
Abstract : A comprehensive study exploring the genetic architecture of the variation in the rice ionome sheds light on the mechanisms controlling mineral nutrient and trace element composition in plants. Abstract: Rice ( Oryza sativa ) is an important dietary source of both essential micronutrients and toxic trace elements for humans. The genetic basis underlying the variations in the mineral composition, the ionome, in rice remains largely unknown. Here, we describe a comprehensive study of the genetic architecture of the variation in the rice ionome performed using genome-wide association studies (GWAS) of the concentrations of 17 mineral elements in rice grain from a diverse panel of 529 accessions, each genotyped at ∼6.4 million single nucleotide polymorphism loci. We identified 72 loci associated with natural ionomic variations, 32 that are common across locations and 40 that are common within a single location. We identified candidate genes for 42 loci and provide evidence for the causal nature of three genes, the sodium transporter gene Os-HKT1;5 for sodium, Os-MOLYBDATE TRANSPORTER1;1 for molybdenum, and Grain number, plant height, and heading date7 for nitrogen. Comparison of GWAS data from rice versus Arabidopsis ( Arabidopsis thaliana ) also identified well-known as well as new candidates with potential for further characterization. Our study provides crucial insights into the genetic basis of ionomic variations in rice and serves as an important foundation for further studies on the genetic and molecular mechanisms controlling the rice ionome.